Faunal remains and environments from the Bronze age of Kalehkoob, Lut Desert, eastern Iran. (December 2018) - Hashemi, Narges; Wood, Rachel; Louys, Julien
Abstract: The study of faunal remains from Kalehkoob, an archeological site in southern Khorasan, Sarayan, represents the first investigation of prehistoric vertebrates in the northern part of the Lut desert, in the east Iranian plateau. A vertebrate assemblage containing >200 specimens was found at various depths (155 cm to 595 cm) of an excavation trench. A combination of morphological and morphometric methods led to the identification of Artiodactyla, namely Bovidae ( Ovis, Gazella, and Bos ) and Perissodactyla, namely Equidae ( Equus asinus and Equus caballus ). Combined zooarcheological and sedimentological analyses points to three phases and two sub phases of depositional. Transition between the second phase and the first and third phases suggests that changes in faunal composition were potentially a response to different environmental conditions during each phase, such as a reduction of river water volume and humidity. Radiocarbon dating of bones from two depths, 155 cm (scapula) and 462 cm (horse tooth) from phases 1 and 2, respectively, provides ages of 3227–3060 cal BP and 5914–5749 cal BP for the deposit. Given the high chemical quality of both samples of scapula and tooth, δ 13 C and δ 15 N analyses were also conducted, suggesting the presence of arid environmental conditions.